(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Two macroeconomic policy options toward achieving a sustainable inflation threshold as well as a stable demand for money function which are capable of fostering pragmatic effort of achieving other macroeconomic goals within the West Africa Monetary Zone (WAMZ) countries, but not much has been achieved. This study examines inflation threshold and demand for money function in the West Africa monetary zone countries, providing insight into attaining the threshold level of inflation that is considered optimally reasonable for maintaining a stable demand for money function. The study employs a quantitative data analysis technique. Data used for this study are annual time series data spanning from 1980-2023 covering the West Africa monetary zone countries. The study employed the autoregressive distributed lag (ARDL) bound testing model to test for time series properties of the relevant data and the vector autoregressive (VAR) model to estimate the threshold level of inflation. Furthermore, error correction modeling (ECM) approach was explored to identify both the short-run and long-run impact of inflation threshold among other major determinants of demand for money function in selected countries in the West African monetary zone. The findings indicate that the expected specified demand for money function was stable and well behaved in the West African Monetary Zones countries. The result further showed that monetary expansion can be both inflationary and deflationary, depending on the country’s economic structure and policy environment.